IMPLEMENTASI STANDAR AKUNTANSI ENTITAS MIKRO KECIL MENENGAH (SAK EMKM) DALAM PENYUSUNAN LAPORAN KEUANGAN UMKM KOTA SUKABUMI - Nurazizah; Zulkarnain , Zulkarnain (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are the most dominating businesses in the world and Indonesia. The development of MSMEs is also quite rapid so that they can become supporters of the economy, especially in Indonesia. To support the development of MSMEs in preparing financial reports, the government issued a special Accounting Standard for Micro, Small, and Medium Entities (SAK EMKM) which is a simple form of General Accounting Standards. This study aims to determine whether MSME Mochi Lampion Sukabumi has implemented SAK EMKM in its financial reporting. The method used in this study is a descriptive qualitative method. Data were obtained from primary and secondary sources. Primary sources are obtained directly through interviews and observations while secondary sources are obtained from documents in the form of photos and notes regarding company profiles. The results showed that MSMEs Mochi Lampion Sukabumi in the process of preparing financial reports had implemented accounting standards such as journaling and cash flow but had not fully implemented SAK EMKM in their financial reporting. Only the preparation of the Income Statement is following SAK EMKM. As for the Statement of Financial Position and Notes to Financial Statements, MSME Mochi Lampion has not yet fully prepared.